Indonesian English Teacher’s Identity: Bridging the Gap between Teachers’ Personal and Professional Identity - Sinom, Patrick Adtya Pratama; Kuswandono, Paulus (Universitas Negeri Semarang, 2022)
Teachers’ personal and professional identities play a crucial role in the learning process. This research aimed to reveal the gap between teachers’ personal and professional identity from the perspective of Indonesian teachers. There were five participants in the research. The participants were selected based on geographical differences. The participants were approached by using virtual media communications. A phenomenological approach with the semi-structured interview was applied to deeply discover and identify teachers’ experiences on personal and professional identity development. Then, thematic analysis was used to put the data into themes. The study revealed that teachers’ personal identity was perceived as individuals’ goals, values, beliefs, actions or behaviour, and interactions in the social-cultural area. Whereas, the professional identity was related to professional competence, teaching ideology, and transferring cultural content and role model. In addition, a teacher’s personal and professional identity are overlapped in terms of identity formation and identity in social interaction. Besides, they are confined by a classroom setting and social context. This research is expected to have a great contribution to teacher identity development, especially for teachers’ personal and professional identity development.